Penguin Sri Aurobindo reader - "Paranjape, Makarand (ed.)" (Gurgaon, 1999)
From the blurb, \"As a writer, Sri Aurobindo's range was staggering; there is hardly a field of human endeavour that escaped his notice. This collection offers a representative sampling of his writings with selections from most of his major works and areas of interest. The volume begins with the early, often-ignored essays written during the struggle for independence, and traces the development of Sri Aurobindo's philosophical and religious thought, culminating in the system of Integral Yoga. Also included are some of his poems, letters and aphorisms. Together, they provide an ideal introduction to the complex and brilliant mind of a remarkable yogi and seer-poet.\" With an introduction by the editor tracing Sri Aurobindo's life and thought.
Keywords: Reference